Wanprestasi dalam Perjanjian Kredit pada Lembaga Perkreditan Desa (LPD) di Desa Bebetin Kecamatan Sawan Kabupaten Buleleng - Kadek Dwinta Pradnyasari; Johannes Ibrahim Kosasih; Desak Gde Dwi Arini (Jurnal Konstruksi Hukum, 2021)
Agreement is the most important source that gives birth to the engagement. One form of engagement in the sources of the agreement is the extension of credit from the bank. This research uses empirical legal research type, data collection techniques in this study using field research. The procedure for granting credit consists of several stages, namely the credit application stage, the location survey stage for prospective debtors, the analysis stage, the decision-making stage, and the credit disbursement stage. The results of the analysis found that the factors that cause default are internal factors and external factors. Internal factors are caused by debtors who are not credible and also unstable economic factors in the midst of the Covid-19 pandemic which caused debtors to be unable to pay arrears in the LPD. External factors from the LPD take a persuasive approach to further handling problematic debtors. The purpose of this study is the procedure for granting credit and binding credit agreements carried out in the LPD Desa Pakraman Bebetin, Sawan District, Buleleng Regency, how are the factors that cause default in LPD Desa Pakraman Bebetin, District of Sawan, District of Buleleng.